Eco-friendly environmental management in integrated and sustainable agricultural systems - Pratiningrum, Marbella (Professorline, 2024)
Integrated and sustainable agriculture is an agricultural system combining various components such as crops, livestock, fish and natural resources to increase efficiency, productivity, farmer welfare and environmental quality. A critical aspect of this agricultural system is environmentally friendly environmental management, which prevents or reduces adverse environmental effects of agricultural activities, such as soil erosion, water pollution, greenhouse gas emissions and biodiversity loss. This article discusses several ecological environmental management strategies in integrated and sustainable agricultural systems, such as organic fertilizer use, crop rotation, agroforestry, water-saving irrigation, integrated pest management and land restoration. The article also highlights some challenges and recommendations for implementing these strategies in Indonesia.